Nutrient, antinutrient and antimicrobial properties of Telfairia Occidentalis pod and biochemical response in experimentally compromised rats’ hematology and lipid profile: https://doi.org/10.51412/psnnjp.2023.26 - Egbuonu, Anthony Cemaluk C.; Alaebo, Prince O.; Atasie, Okechukwu C.; Obike, Chiemeziem A.; Nsofor, Onuoha U.; Okonkwo, Cynthia I.; Mathews, Chukwuma E.; Inya, Mayor D. (The Nigerian Journal of Pharmacy, 2023)
Background: Recent study indicated the prospective use of the essentially unutilized pod of Telfairia Occidentalis (TOP), in dietary management of monosodium glutamate, MSG, related hepatotoxicity. This study aimed to determine some minerals, vitamins, antinutrients and antimicrobial properties of TOP flour ethanol extract (TOPE) and to evaluate its hematologic and lipid profile responses against MSG intoxication in rats Methods: The in vitro determination of minerals, vitamins, anti-nutrients and antimicrobial properties of TOP by standard referenced protocols were carried out. Twenty adult male Wistar rats (120 - 175 g) randomly allotted to five groups of 4 rats each in groupsA, B, C, D and E respectively received normal saline (1 mL), via oral gavage and daily for 14 days. The evaluation of some hematologic (red blood cell, RBC, packed cell volume, PCV and hemoglobin, HB) and lipid (triacylglycerol, TAG, low density lipoprotein cholesterol, LDL-Chol, high density lipoprotein cholesterol, HDL-Chol and total cholesterol, T-Chol) profile responses followed standard and referenced protocols. Results: The results revealed that TOPE is composed of important bioactive minerals, vitamins and anti-nutrients mix with in vitro concentration-dependent antimicrobial activity. In vivo, TOPE compared favourably with the control and elicited a significant (P < 0.05) and dose-dependent mitigation of the associated dysfunctions caused by MSG intoxication in rats’ hematologic and lipid profiles. Conclusion: TOPE demonstrated dietary property and concentration-dependent antimicrobial activity. In vivo, TOPE improved hematologic and lipid profile functions in the rats and corrected apparent disruptions associated with MSG intoxication in rats via probable blood boosting and lipid lowering activities. The implications of these findings warrant follow up as they may be significant in relation to prospective application of TOPE as potential novel diet and drug for the resistance of microbial pathogens and the modulation of MSG-related disruptions in animal hematology and lipid metabolism